2023
DOI: 10.3390/molecules28165972
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/SnS/CoS Heterostructures on Graphene: Lattice-Confinement Synthesis and Boosted Sodium Storage

Abstract: The development of high-efficiency multi-component composite anode nanomaterials for sodium-ion batteries (SIBs) is critical for advancing the further practical application. Numerous multi-component nanomaterials are constructed typically via confinement strategies of surface templating or three-dimensional encapsulation. Herein, a composite of heterostructural multiple sulfides (MoS2/SnS/CoS) well-dispersed on graphene is prepared as an anode nanomaterial for SIBs, via a distinctive lattice confinement effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This result can positively corroborate the effective role of the atomic heterointerface and PPy as a protecting layer to alleviate the structural collapse. We compared previous similar experiments in Table S1 [ 39 , 43 , 44 , 45 , 46 , 47 ]. It was found that the rate capacities and cyclic stability of Mo 3 S 4 /CoMo 2 S 4 -30PPy are improved, indicating the superiority of our designs.…”
Section: Resultsmentioning
confidence: 99%
“…This result can positively corroborate the effective role of the atomic heterointerface and PPy as a protecting layer to alleviate the structural collapse. We compared previous similar experiments in Table S1 [ 39 , 43 , 44 , 45 , 46 , 47 ]. It was found that the rate capacities and cyclic stability of Mo 3 S 4 /CoMo 2 S 4 -30PPy are improved, indicating the superiority of our designs.…”
Section: Resultsmentioning
confidence: 99%